Tranexamic acid in radical cystectomy: a systematic review and meta-analysis of efficacy and safety - Mangold, Maurin Helen; Wieland, Victoria; Grilli, Maurizio; Studier-Fischer, Alexander; Haney, Caelán Max; Westhoff, Niklas Christian; Michel, Maurice Stephan; Egen, Luisa; Kowalewski, Karl-Friedrich (World journal of urology, 2025)
Radical cystectomy (RC) is a high-risk procedure, associated with significant bleeding and high risk of perioperative blood transfusion (PBT), which may limit clinical and oncological outcomes. Tranexamic acid (TXA), an antifibrinolytic agent, effectively reduces bleeding in various surgical settings; however, its role in RC remains understudied. This systematic review and meta-analysis evaluates the efficacy and safety of TXA in RC patients.
Gesehen am 27.10.2025